Late-stage catalysis of rapid room temperature polymerization
By uniformly deposition of catalyst combinations in the mold and on the surface of the optical filter element, the problem of early gelation of high-speed room temperature polymer soluble combinations during rapid filling and molding is solved, and the stability and optical performance of the substrate are improved.
Patent Information
- Application Number
- JP2024556754
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-31
- Filing Date
- 2023-03-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-03-29
AI Technical Summary
The existing high-speed room temperature polymer soluble combinations can easily lead to early gelation during rapid filling and molding, resulting in a decrease in the stability of the substrate.
Using a method, the method includes providing a high-speed room temperature polymer soluble combination and catalyst combination, and uniformly depositing the catalyst combination on the inner surface of the mold and the surface of the light filter element, ensuring that the polymer soluble combination reacts sufficiently within the mold and forms a transparent solid substrate.
By extending the expiration of polymer soluble combinations and avoiding early gelation, the stability and optical properties of the substrate are improved, ensuring the quality of manufacturing optical articles such as glasses lenses.
Smart Images

Figure 2025510851000001 
Figure 2025510851000002 
Figure 2025510851000003
Abstract
Description
[Technical field]
[0001] The present invention provides a method for fast curing of fast room temperature polymerizable compositions to obtain transparent substrates, especially optical substrates such as lenses, especially ophthalmic lenses. [Background technology]
[0002] Transparent plastic substrates are well known and commonly used in the manufacture of optical articles such as ophthalmic lenses.To manufacture such transparent plastic substrates, plastic substrates made of thermosetting polymers obtained by polymerization of polymerizable compositions containing monomers and / or oligomers that can be polymerized under heat-activated conditions to form polymers can be used.Usually, in the ophthalmic field, thermosetting polymers have a polymer network structure that is irreversibly formed by chemical reaction of monomers under heat-activated conditions.
[0003] The objective of the present invention is to obtain, at room temperature, from a polymerizable composition, a transparent plastic substrate that can be used to manufacture optical articles such as ophthalmic lenses. By avoiding thermal activation, the manufacturing process is simplified and more environmentally friendly, and less complex equipment is required.
[0004] Examples of fast room temperature polymerizable compositions are described in U.S. Patent Nos. 6,887,401 and 5,973,098, both of which describe methods for producing cast transparent polythiourethane substrates that can be used to make optical articles. The techniques described in US Patents 5,973,098 and 6,887,401 are similar and involve short mixing times of the monomers or prepolymers involved in the polymerization reaction with the catalyst, and describe a method in which one of the monomers or prepolymers involved in the polymerization reaction is first mixed with a catalyst solution, and then said mixture is mixed with the remaining monomers or prepolymers to form a further mixture, which is then immediately filled into the mold cavity.
[0005] However, to avoid loss of stability, the addition of the catalyst solution to one of the monomers or prepolymers must be immediately followed by the addition of the remaining monomer or prepolymer. The resulting mixture containing both monomers or prepolymers and catalyst must be rapidly filled into the mold cavity to avoid premature gelation during mixing or filling. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] U.S. Pat. No. 5,973,098 [Patent Document 2] U.S. Patent No. 6,887,401 Summary of the Invention [Problem to be solved by the invention]
[0007] Thus, there is a need to extend the duration of effectiveness of rapidly room temperature polymerizable compositions. [Means for solving the problem]
[0008] The present invention relates to a method for fast curing a transparent cast substrate that can be used to manufacture optical articles such as ophthalmic lenses, the method comprising: - providing a fast room temperature polymerizable composition; - providing a catalyst composition; - providing a mold assembly including two non-sealing molds each having an inner surface and an outer surface, and optionally providing an optical filtering element disposed or configured to be disposed between the two non-sealing molds; - a catalyst composition, on at least one inner surface of the mold, and / or - on at least one surface of an optical filtering element that is subsequently disposed within the mold assembly. and depositing the - closing the mold assembly such that the inner surfaces of the two non-closed molds together form a molding cavity; - filling a mold cavity of a mold assembly that already contains a catalyst composition deposited on at least one inner surface of the mold with a fast room temperature polymerizable composition; - curing the filled mold assembly to obtain a transparent solid substrate, a) a first step for polymerizing said rapidly room temperature polymerizable composition at room temperature to obtain a gel; b) a second step of post-curing the gel to obtain a transparent solid substrate; and - recovering the transparent solid substrate from the mold assembly; Includes.
[0009] According to one embodiment, the step of depositing the catalyst composition onto at least one interior surface of the mold and / or onto at least one side of the light filtering element is performed by liquid deposition.
[0010] According to one embodiment, the step of depositing the catalyst composition onto at least one inner surface of the mold and / or onto at least one side of the light filtering element is performed by spin coating, dip coating, spray coating, brush coating or roller coating.
[0011] According to one embodiment, the rapid room temperature polymerizable composition has a viscosity in the range of 0.1 to 0.3 Pa·s at 25°C.
[0012] According to one embodiment, the fast room temperature polymerizable composition comprises (a) at least one poly(iso)thiocyanate monomer or liquid NCO- or NCS-terminated poly(thio)urethane prepolymer, and at least one polythiol monomer or liquid SH-terminated poly(thio)urethane prepolymer; or (b) one or more polymerizable episulfide compounds The composition is selected from the group consisting of:
[0013] According to one embodiment, the mixture (a) comprises - a first component A comprising a polythiourethane prepolymer having isocyanate or isothiocyanate (NCX, where X is O or S) end groups and a viscosity in the range of 0.02 to 0.4 Pa·s at 25°C; a second component B comprising a polythiourethane prepolymer having thiol (SH) end groups and a viscosity in the range of 0.2 to 2.0 Pa·s at 25°C; Including, Components A and B are obtained by polymerizing at least one polyisocyanate or polyisothiocyanate monomer and at least one polythiol monomer.
[0014] According to one embodiment, the amounts of polyisocyanate or polyisothiocyanate monomers and polythiol monomers are such that the ratio NCX / SH in the mixture of polyisocyanate or isothiocyanate monomers and polythiol monomers ranges from 4:1 to 30:1 to obtain component A, and the ratio SH / NCX in the mixture of polyisocyanate or isothiocyanate monomers and polythiol monomers ranges from 4:1 to 30:1 to obtain component B.
[0015] According to one embodiment, the polythiol is an organic group having the formula: R'(SH)n', where n' is an integer from 2 to 6, preferably 3 to 4, and R' has a valence equal to n'.
[0016] According to one embodiment, the polythiol is pentaerythritol tetrakis mercaptopropionate, 1-(1'mercaptoethylthio)-2,3-dimercaptopropane, 1-(2'-mercaptopropylthio)-2,3-dimercaptopropane, 1-(-3'mercaptopropylthio)-2,3-dimercaptopropane, 1-(-4'mercaptobutylthio)-2,3-dimercaptopropane, 1-(5'mercaptopentylthio)-2,3-dimercaptopropane, 1-(6'-mercaptohexylthio)-2,3-dimercaptopropane, 1,2-bis(-4'-mercaptobutylthio)-3-mercaptopropane, 1,2-bis(-5'mercaptopentylthio)-3-mercaptopropane, 1,2-bis(-6'-mercaptohexylthio)-2,3-dimercaptopropane, 1,2-bis(-6'-mercaptohexylthio)-2,3-dimercaptopropane, 1,2-bis(-6'-mercaptohexylthio)-3- ... 1,2,3-tris(-mercaptohexyl)-3-mercaptopropane, 1,2,3-tris(mercaptomethylthio)propane, 1,2,3-tris(-3'-mercaptopropylthio)propane, 1,2,3-tris(-2'-mercaptoethylthio)propane, 1,2,3-tris(-4'-mercaptobutylthio)propane, 1,2,3-tris(-6'-mercaptohexylthio)propane, methanedithiol, 1,2-ethanedithiol, 1,1-propanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 2,2-propanedithiol, 1,6-hexanethiol-1,2,3-propanetrithiol and 1,2-bis(-2'-mercaptoethylthio)-3-mercaptopropane.
[0017] According to one embodiment, the polyisocyanate or polyisothiocyanate has the formula: [ka] is selected from monomers of the formula: R 1 are independently H or a C1-C5 alkyl group, preferably CH3 or C2H5; R 2 is H, a halogen, preferably Cl or Br, or a C1-C5 alkyl group, preferably CH3 or C2H5, Z is -N=C=X, where X is O or S; a is an integer ranging from 1 to 4, b is an integer ranging from 2 to 4, and a+b≦6; and x is an integer of 1 to 10, preferably 1 to 6.
[0018] According to one embodiment, the polyisocyanate or isothiocyanate is selected from the group consisting of tolylene diisocyanate or diisothiocyanate, phenylene diisocyanate or diisothiocyanate, ethyl phenylene diisocyanate, isopropyl phenylene diisocyanate or diisothiocyanate, dimethyl phenylene diisocyanate or diisothiocyanate, diethyl phenylene diisocyanate or diisothiocyanate, diisopropyl phenylene diisocyanate or diisothiocyanate, trimethyl benzyl triisocyanate or triisothiocyanate. diisocyanate, xylylene diisocyanate or diisothiocyanate, benzyl triiso(thio)cyanate, 4,4'-diphenylmethane diisocyanate or diisothiocyanate, naphthalene diisocyanate or diisothiocyanate, isophorone diisocyanate or diisothiocyanate, bis(isocyanate or isothiocyanatomethyl)cyclohexane, hexamethylene diisocyanate or diisothiocyanate, and dicyclohexylmethane diisocyanate or diisothiocyanate.
[0019] According to one embodiment, the fast room temperature polymerizable composition has the formula: [ka] wherein X is S or O.
[0020] According to one embodiment, the light filtering element is selected from a polarizing film, a polarizing laminate, a photochromic film, a photochromic laminate, a near infrared filter, a near infrared laminate, a blue cut filter, a blue cut laminate, a microstructured film, and a microstructured laminate.
[0021] According to one embodiment, the catalytic composition consists of a tertiary amine, such as triethylamine, an organometallic compound, such as dibutyltin dilaurate, and a compound chosen from alkali metal, alkaline earth metal, transition metal and ammonium salts of acids or mixtures thereof, the salts of which satisfy the condition 0.5≦pKa≦14.
[0022] The present invention further relates to an optical article produced by the above method.
[0023] Without being limited in the general manner described herein above, further details relating to various embodiments of the invention are described in the Detailed Description of the Invention section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] In the following description, the making and use of various embodiments will be discussed in detail below, but it should be understood that as described herein, many inventive concepts are provided that can be embodied in a variety of contexts. The embodiments discussed herein are merely representative and do not limit the scope of the present invention. It will also be apparent to those skilled in the art that all technical features defined in relation to the method can be replaced by the device, either individually or in combination, and conversely, all technical features related to the device can be replaced by the method, either individually or in combination.
[0025] Words or terms used in this specification have their plain and ordinary meaning in the field of this disclosure, unless expressly and clearly defined in this disclosure or unless a different meaning is required by a particular context.
[0026] In the event of any conflict in the usage of a word or term in this disclosure and one or more patents or other documents that may be incorporated by reference, the non-conflicting definition in this specification shall control.
[0027] The words "comprise," "contain," "include," "have" and all grammatical variations thereof are intended to have an open, non-limiting meaning. For example, a composition that includes an ingredient does not exclude additional ingredients, a device that includes a part does not exclude additional parts, and a method that includes a step does not exclude additional steps. When such terms are used, compositions, devices, and methods that "consist essentially of" or "consist of" the specified ingredients, parts, and steps are specifically included and disclosed. As used herein, the term "consist essentially of" and all grammatical variations thereof are intended to limit the claims to the specified materials or steps and those that do not materially affect the basic and novel characteristics of the invention as recited in the claims.
[0028] The indefinite article "a" or "an" means one or more of the ingredients, parts or steps introduced by the article.
[0029] Whenever a numerical range of a degree or measurement having a lower and upper limit is disclosed, any number and any range encompassed within the range is also intended to be specifically disclosed. For example, all ranges of values (such as "a to b" or "about a to about b" or "about a to b," "approximately a to b," and any similar expression in which "a" and "b" represent the numerical values of a degree or measurement) should be understood to refer to all numbers and ranges encompassed within the broader range of values, including the exact values of "a" and "b."
[0030] Terms such as "first", "second", "third", etc. may be assigned arbitrarily and are merely intended to distinguish between two or more components, parts or steps that are otherwise similar or corresponding in nature, structure, function or action. For example, the words "first" and "second" serve no other purpose and are not part of the name or description of the subsequent name or description. The mere use of the term "first" does not require that there be any "second" similar or corresponding component, part or step. Similarly, the mere use of the word "second" does not require that there be any "first" or "third" similar or corresponding component, part or step. Furthermore, it should be understood that the mere use of the term "first" does not require that an element or step be the very first in any sequence, but merely that it must be at least one of the elements or steps. Similarly, the mere use of the terms "first" and "second" does not require any sequence. As such, the mere use of such terms does not exclude intervening elements or steps between a "first" and a "second" element or step.
[0031] As used herein, polymerization / polymerizing / polymerizable refers to a chemical reaction that produces the combination of two or more monomers and / or oligomers to form a polymer. Polymerization and all grammatical variations thereof include photopolymerizable compositions and / or thermally polymerizable compositions. Photopolymerizable refers to polymerization that occurs by exposing the composition to activating light. Thermally polymerizable refers to polymerization that occurs by exposing the composition to a change in temperature.
[0032] As used herein, curing refers to the chemical process of converting monomers or oligomers into polymers having higher molecular weight and then into networks.
[0033] As used herein, "monomer" and / or "oligomer" refer to a chemical compound that contains at least one reactive group that can react in the presence of an initiator or catalyst. Further details relating to the "reactive groups" involved are provided later in this specification.
[0034] As used herein, "prepolymer" refers to a monomer or monomer system that has been reacted to an intermediate molecular weight state. This material can be further polymerized through reactive groups to a fully cured, high molecular weight state. Thus, a mixture of reactive polymer and unreacted monomer can also be called a prepolymer. The terms "prepolymer" and "polymer precursor" can be synonymous.
[0035] As used herein, "viscosity" refers to a fluid's resistance to deformation.
[0036] As used herein, "fast room temperature polymerizable composition" or "fast-setting room temperature polymerizable composition" may be used interchangeably and refer to a composition that cures at room temperature within 10 minutes. In other words, the composition gels in such a way that a hard gel is obtained within a short time and at room temperature. Formation of a hard gel means that the resulting polymerized composition is self-supporting, i.e., it holds its own shape without deformation.
[0037] As used herein, an ophthalmic lens is understood to be transparent when the viewing of an image through said ophthalmic lens is perceived without significant loss of contrast, i.e. when the formation of an image through said ophthalmic lens is obtained without adversely affecting the quality of the image. This definition of the term "transparent" may be applied within the scope of this disclosure to all objects so modified herein.
[0038] The posterior surface (generally the concave surface) of the lens substrate is the surface of the lens substrate that is closest to the wearer's eye when in use. The anterior surface (generally the convex surface) of the lens substrate is the surface of the lens substrate that is furthest from the wearer's eye when in use.
[0039] According to a first aspect, the present invention relates to a method for fast curing a transparent cast substrate that can be used to manufacture optical articles such as ophthalmic lenses, the method comprising the steps of: - providing a fast room temperature polymerizable composition; - providing a catalyst composition; - providing a mold assembly including two non-sealing molds each having an inner surface and an outer surface, and optionally providing an optical filtering element disposed or configured to be disposed between the two non-sealing molds; - a catalyst composition, on at least one inner surface of the mold, and / or - on at least one surface of an optical filtering element that is subsequently disposed within the mold assembly. and depositing the - closing the mold assembly such that the inner surfaces of the two non-closed molds together form a molding cavity; - filling a mold cavity of a mold assembly that already contains a catalyst composition deposited on at least one inner surface of the mold with a fast room temperature polymerizable composition; - curing the filled mold assembly to obtain a transparent solid substrate, a) a first step for polymerizing said composition at room temperature to obtain a gel; b) a second step of post-curing the gel to obtain a transparent solid substrate; and - recovering the transparent solid substrate from the mold assembly; Includes.
[0040] The process includes providing a mold assembly that includes two non-enclosed molds, each having an inner surface and an outer surface.
[0041] The mold assembly, which includes two non-closed molds each having an inner surface and an outer surface, serves as a template for the final shape of the substrate. The forming cavity thus defines said final shape. According to one embodiment, the forming cavity has a curved shape in order to finally obtain a substrate having a concave surface and a convex surface. The inner surfaces of the two parts of the mold are thus respectively curved, one presenting a convex surface and the other a concave surface. Thus, the inner surfaces of the two non-closed molds constituting the casting assembly correspond to the surfaces forming the forming cavity.
[0042] Optionally, an optical filtering element may be disposed between the two non-sealing molds. An optical filtering element may be disposed between the two non-sealing molds, between the inner surfaces of the two non-sealing molds.
[0043] The catalyst composition can be deposited in the molded cavity prior to adding the fast room temperature polymerizable composition in a variety of ways.
[0044] According to one embodiment, the catalyst composition is deposited within the molding cavity on one of the interior surfaces of the mold parts that form the mold assembly.
[0045] According to one embodiment, the catalyst composition is deposited within the molding cavity on both of the interior surfaces of the mold parts that form the mold assembly.
[0046] According to one embodiment, the catalytic composition is deposited on one face or surface of a light filtering element that is subsequently added within the molded cavity.
[0047] According to one embodiment, the catalytic composition is deposited on both surfaces of a light filtering element that is subsequently added within the molded cavity.
[0048] According to one embodiment, the catalyst composition is deposited within the mold cavity on one of the inner surfaces of the mold parts that form the mold assembly and on one of the surfaces of a light filtering element that is later added into the mold cavity.
[0049] According to one embodiment, the catalyst composition is deposited within the mold cavity both on one of the inner surfaces of the mold parts that form the mold assembly and on the surface of a light filtering element that is later added into the mold cavity.
[0050] According to one embodiment, the catalyst composition is deposited within the mold cavity on both of the inner surfaces of the mold parts that form the mold assembly and on one of the surfaces of a light filtering element that is later added into the mold cavity.
[0051] According to one embodiment, the catalyst composition is deposited within the mold cavity on both the inner surfaces of the mold parts that form the mold assembly and on the surface of a light filtering element that is later added into the mold cavity.
[0052] According to one embodiment, the light filtering element is first provided between two non-closed mold parts forming the mold assembly, and then the catalyst composition is deposited in the molding cavity on one of the inner surfaces of the mold parts forming the mold assembly.
[0053] According to one embodiment, the light filtering element is first provided between two non-closed mold parts forming the mold assembly, and then the catalyst composition is deposited in the molding cavity on both of the inner surfaces of the mold parts forming the mold assembly.
[0054] According to one embodiment, the light filtering element is first provided on one of the inner surfaces of the mold parts that form the mold assembly, and then the catalyst composition is deposited in the molding cavity on the remaining inner surface of the mold parts that form the mold assembly.
[0055] According to one embodiment, the light filtering element is first provided on one of the inner surfaces of the mold parts forming the mold assembly, and then the catalyst composition is deposited in the molding cavity on the remaining inner surfaces of the mold parts forming the mold assembly and on the surface of the light filtering element.
[0056] According to one embodiment, the light filtering element is first provided on one of the inner surfaces of the mold parts forming the mold assembly. The catalyst composition is then deposited on the surface of the light filtering element within the mold cavity.
[0057] According to one embodiment, the step of depositing the catalyst composition onto at least one interior surface of the mold and / or onto at least one side of the light filtering element is performed by liquid deposition.
[0058] According to one embodiment, the step of depositing the catalyst composition onto at least one inner surface of the mold and / or onto at least one side of the light filtering element is performed by spin coating, dip coating, spray coating, brush coating or roller coating.
[0059] Generally, the thickness of the layer of the catalyst composition is in the range of 0.5 to 20 μm. According to one embodiment, the thickness of the layer of the catalyst composition is in the range of 1 to 20 μm, or 1 to 5 μm, or 1 to 3 μm.
[0060] The composition of the present disclosure is highly reactive at room temperature and can give a gel within a polymerization time of 1 to 60 minutes. According to one embodiment, the composition of the present disclosure has a short gelation time of 1 to 5 minutes.
[0061] The present disclosure therefore relates to a process for producing cast substrates such as optical articles, in particular lenses, without pot life problems, by mixing the required amounts of each of the components of the composition according to the present disclosure as described above, other than the catalyst, just prior to casting.
[0062] A conventional mold typically includes two pieces (referred to herein as parts) made of mineral glass, around the periphery of which is disposed an annular closure member, such as a gasket or adhesive tape, thereby defining the required molding cavity.
[0063] According to one embodiment, the polymerized composition is self-supporting in the two-part mold assembly when the annular closure of the mold assembly is removed.
[0064] Typically, the filling of the mold cavity is performed using a pipe connected to a pressurized molded material reservoir and attached to the casting opening like a filling nozzle. Syringe filling can be used, coupled to an electric or pneumatic device. In this way, the exact amount of composition can be easily adjusted and fixed for precise delivery. With such a method, it is possible to start the polymerization immediately after filling.
[0065] A gel is obtained in a short time and at room temperature. The gel formation inside the mold takes place at room temperature and has a duration ranging from 1 to 60 minutes or from 1 to less than 15 minutes, typically about 10 minutes, although shorter gelling times of 1 to 5 minutes may still be preferred.
[0066] The gel is then cured at elevated temperature in an oven (e.g., an air oven) to complete the polymerization. Polymerization is generally carried out at temperatures ranging from 50-150° C. or 100-130° C. and typically lasts for 2-4 hours. According to one embodiment, the mold assembly is placed in an air oven and heated at 120° C. for 2 hours.
[0067] The mold assembly is then removed from the oven, the annular closure member is removed, and the mold parts are disassembled to recover the substrate, which can then be edged to obtain the finished lens.
[0068] The substrate or article may then be pigmented, coated to improve scratch resistance, anti-reflective treatments may be added, and microstructured films and laminates may be added, as described below.
[0069] Rapidly room temperature polymerizable compositions useful in the present disclosure According to one embodiment, the rapid room temperature polymerizable composition has a viscosity in the range of 0.1 to 0.3 Pa·s at 25°C.
[0070] One major problem associated with molding processes, especially those for producing optical substrates such as ophthalmic lenses, is obtaining a substrate free of defects, especially free of striations. If the viscosity of the liquid monomer mixture is relatively low, i.e. less than 3.10-3 Pa·s at 25°C, the time to gel is relatively long. In that case, localized heat points that appear in the mixture during polymerization will cause convection, resulting in so-called "convection-induced striations" in the final polymerized substrate.
[0071] The rate of formation of such convection-induced striations increases as the mixture viscosity decreases, whereas simple filling of the mold cavity with the monomer mixture results in the formation of so-called "filling-induced striations". The relaxation time required to remove such fill-induced striations increases as the monomer mixture viscosity increases.
[0072] Furthermore, when relatively high viscosity monomer mixtures are used, it is difficult to remove air bubbles that may become trapped within the liquid monomer mixture.
[0073] As a result, the rapid room temperature polymerizable composition according to the present disclosure having a viscosity of 0.1-0.3 Pa·s at 25° C. improves the shortcomings of the prior art methods, and thus makes it possible to obtain transparent cast substrates that are substantially free of optical defects, in particular convection and / or fill-induced striations.
[0074] According to the present disclosure, the fast room temperature polymerizable composition comprises: (a) at least one poly(iso)thiocyanate monomer or liquid NCO- or NCS-terminated poly(thio)urethane prepolymer, and at least one polythiol monomer or liquid SH-terminated poly(thio)urethane prepolymer; or (b) one or more polymerizable episulfide compounds The composition is selected from the group consisting of:
[0075] Therefore, the rapidly room-temperature polymerizable composition (a) is (i) at least one poly(iso)thiocyanate monomer and at least one polythiol, or (ii) a mixture of at least one liquid NCO- or NCS-terminated poly(thio)urethane prepolymer and at least one liquid SH-terminated poly(thio)urethane prepolymer, or (iii) at least one poly(iso)thiocyanate monomer and at least one liquid SH-terminated poly(thio)urethane prepolymer, or (iv) at least one polythiol and at least one liquid NCO- or NCS-terminated poly(thio)urethane prepolymer is a mixture selected from:
[0076] mixture (a)(i) According to one embodiment, the fast room temperature polymerizable composition is selected from at least one poly(iso)thiocyanate monomer and at least one polythiol.
[0077] As used herein, poly(iso)thiocyanate monomer refers to either polyisocyanates or polyisothiocyanate monomers.
[0078] The fast room temperature polymerizable composition containing at least one poly(iso)thiocyanate monomer and at least one polythiol has a viscosity in the range of 0.1 to 0.3 Pa·s at 25°C.
[0079] The NCX / SH and SH / NCX ratios are in the range of 6:1 to 10:1. The amounts of polyisocyanate or polyisothiocyanate monomers and polythiol monomers are such that the ratio NCX / SH for the mixture of polyisocyanate or isothiocyanate monomers and polythiol monomers is in the range of 4:1 to 30:1. The NCX / SH and SH / NCX ratios can be in the range of 6:1 to 10:1.
[0080] The polyisocyanate or isothiocyanate monomer can be any polyisocyanate or isothiocyanate monomer having two or more isocyanate or isothiocyanate functional groups per molecule, or two or three isocyanate or isothiocyanate functional groups, or two isocyanate or isothiocyanate functional groups.
[0081] According to one embodiment, the polyisocyanate or isothiocyanate monomer has the formula: [ka] wherein R 1 are independently H or a C1-C5 alkyl group, R 2 is H, halogen or a C1-C5 alkyl group, Z is -N=C=X, where X is O or S; a is an integer ranging from 1 to 4, b is an integer ranging from 2 to 4, and a+b≦6; and and x is an integer from 1 to 10.
[0082] According to one embodiment, R 1 is independently CH3 or C2H5.
[0083] According to one embodiment, R 2 is chlorine or bromine.
[0084] According to one embodiment, R 2 is CH3 or C2H5.
[0085] According to one embodiment, Z is -N=C=X, wherein X is O.
[0086] According to one embodiment, x is an integer from 1 to 6.
[0087] Among the polyisocyanate or isothiocyanate monomers, tolylene diisocyanate or diisothiocyanate, phenylene diisocyanate or diisothiocyanate, ethyl phenylene diisocyanate, isopropyl phenylene diisocyanate or diisothiocyanate, dimethyl phenylene diisocyanate or diisothiocyanate, diethyl phenylene diisocyanate or diisothiocyanate, diisopropyl phenylene diisocyanate or diisothiocyanate, trimethyl benzyl triisocyanate or triisothiocyanate, xylylene diisocyanate or diisothiocyanate, benzyl triiso(thio)cyanate, 4,4'-diphenylmethane diisocyanate or diisothiocyanate, naphthalene diisocyanate or diisothiocyanate, isophorone diisocyanate or diisothiocyanate, bis(isocyanate or diisothiocyanatemethyl)cyclohexane, hexamethylene diisocyanate or diisothiocyanate, and dicyclohexylmethane diisocyanate or diisothiocyanate.
[0088] According to one embodiment, the polyisocyanate monomer is xylylene diisocyanate and the polythiol monomer is 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane-1-thiol.
[0089] A single polyisocyanate or isothiocyanate monomer or mixtures thereof may also be used.
[0090] The polythiol monomer can be any suitable polythiol having two or more thiol functional groups. It can have two or three thiol functional groups.
[0091] The polythiol monomer can be represented by the formula R'(SH)n', where n' is an integer from 2 to 6, and R' is an organic group of valence equal to n'. n' can be an integer from 3 to 4.
[0092] Useful polythiol monomers are those disclosed in EP-A-394.495 and US Pat. No. 4,775,733 and polythiols corresponding to the formula: [ka]
[0093] Among the polythiol monomers, pentaerythritol tetrakis mercaptopropionate, 1-(1'mercaptoethylthio)-2,3-dimercaptopropane, 1-(2'-mercaptopropylthio)-2,3-dimercaptopropane, 1-(-3'mercaptopropylthio)-2,3-dimercaptopropane, 1-(-4'mercaptobutylthio)-2,3-dimercaptopropane, 1-(5'mercaptopentylthio)-2,3-dimercaptopropane, 1-(6'-mercaptohexylthio)-2,3-dimercaptopropane, 1,2-bis(-4'-mercaptobutylthio)-3-mercaptopropane, 1,2-bis(-5'mercaptopentylthio)-3-mercaptopropane, 1,2-bis(-6'-mercaptohexylthio)-2,3-di ... aliphatic polythiols such as 1,2,3-tris(mercaptomethylthio)propane, 1,2,3-tris(-3'-mercaptopropylthio)propane, 1,2,3-tris(-2'-mercaptoethylthio)propane, 1,2,3-tris(-4'-mercaptobutylthio)propane, 1,2,3-tris(-6'-mercaptohexylthio)propane, methanedithiol, 1,2-ethanedithiol, 1,1-propanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 2,2-propanedithiol, 1,6-hexanethiol-1,2,3-propanetrithiol, and 1,2-bis(-2'-mercaptoethylthio)-3-mercaptopropane.
[0094] According to one embodiment, the polythiol is 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane-1-thiol. [ka]
[0095] Polythiol has a molecular weight of 2·10 at 25°C. -1 Pa s or less, or 10 -1 Pa s or less, or 0.5 10 -1 It has a viscosity of less than Pa·s.
[0096] Mixture (a)(ii) According to one embodiment, the fast room temperature polymerizable composition is selected from a mixture of at least one liquid NCO or NCS terminated poly(thio)urethane prepolymer and at least one liquid SH terminated poly(thio)urethane prepolymer.
[0097] The mixture (ii) is - a first component A comprising a polythiourethane prepolymer having isocyanate or isothiocyanate (NCX, where X is O or S) end groups and a viscosity in the range of 0.02 to 0.4 Pa·s at 25°C; - a second component B comprising a polythiourethane prepolymer having thiol (SH) end groups and a viscosity in the range of 0.2 to 2.0 Pa·s at 25°C; Including, Components A and B are obtained by polymerizing at least one polyisocyanate or polyisothiocyanate monomer and at least one polythiol monomer.
[0098] The polyisocyanate or isothiocyanate monomer useful for making the prepolymer components A and B can be any polyisocyanate or isothiocyanate monomer having two or more isocyanate or isothiocyanate functional groups per molecule, preferably two or three isocyanate or isothiocyanate functional groups, and more preferably two isocyanate or isothiocyanate functional groups.
[0099] Components A and B are obtained by polymerizing at least one polyisocyanate or polyisothiocyanate monomer and at least one polythiol monomer similar to the monomers having the formula detailed above for mixture (a)(i).
[0100] The polymerization methods are conventional, but the amounts of polyisocyanate or isothiocyanate monomers and polythiol monomers in the reaction medium shall be adapted in each case. Typically, components A and B can be prepared by conventional thermal polymerization, including induction heating and infrared heating.
[0101] Ingredient A Component A comprises a polythiourethane prepolymer having isocyanate or isothiocyanate (NCX, where X is O or S) end groups and a viscosity in the range of 0.02 to 0.4 Pa·s at 25°C.
[0102] Component A is obtained by polymerizing at least one polyisocyanate or polyisothiocyanate monomer and at least one polythiol monomer similar to those detailed above for mixture (a)(i).
[0103] The amounts of polyisocyanate or polyisothiocyanate monomer and polythiol monomer are such that the ratio NCX / SH for the mixture of polyisocyanate or isothiocyanate monomer and polythiol monomer is in the range of 4:1 to 30:1 to obtain component A.
[0104] Thus, component A may have a molar ratio of isocyanate or isothiocyanate groups to thiol groups, NCX / SH, in the range of 4:1 to 30:1.
[0105] According to one embodiment, the NCX / SH ratio is in the range of 6:1 to 10:1.
[0106] Component B Component B comprises a polythiourethane prepolymer having thiol (SH) end groups and a viscosity in the range of 0.2 to 2.0 Pa·s at 25°C.
[0107] Component B is obtained by polymerizing at least one polyisocyanate or polyisothiocyanate monomer and at least one polythiol monomer, similar to those detailed above for mixture (a)(i).
[0108] The amounts of polyisocyanate or polyisothiocyanate monomer and polythiol monomer are such that the ratio SH / NCX for the mixture of polyisocyanate or isothiocyanate monomer and polythiol monomer is in the range of 4:1 to 30:1 to obtain component B.
[0109] Thus, component B may have a molar ratio of thiol groups to isocyanate or isothiocyanate groups, SH / NCX, in the range of 4:1 to 30:1.
[0110] According to one embodiment, the SH / NCX ratio is in the range of 6:1 to 10:1.
[0111] The preparation of prepolymers having thiol end groups has been previously described in U.S. Patent No. 6,887,401. A similar process can be used to prepare component B of the present disclosure.
[0112] Component A of the present disclosure can be prepared in a similar manner, but with the required ratio of polyisocyanate or isothiocyanate to polythiol monomer to obtain a polythiourethane prepolymer with isocyanate or isothiocyanate end groups, a detailed example of which is shown below.
[0113] In certain embodiments, the rapidly room temperature polymerizable composition of the present disclosure is in the form of a two-component polymerizable composition, i.e., a composition formulated as two separate components that are mixed together immediately prior to use.
[0114] In this two-component embodiment, the composition comprises a first separate component or premix containing all of the polyiso(thio)cyanate monomer, optionally some or all of the polythiol monomer, and optionally a UV absorber and a mold release agent, and a second separate component or premix comprising some or all of the polythiol monomer and optionally a solvent.
[0115] In this two-component embodiment of the composition of the present disclosure, the first premix comprises: 40 to 100 parts by weight of a polyiso(thio)cyanate monomer; 0 to 60 parts by weight of a polythiol monomer; 0 to 0.3 parts by weight of a UV absorber; 0 to 0.2 parts by weight of an internal release agent; and the second premix comprises: 0 to 100 parts by weight of a polythiol monomer; 0 to 1 part by weight of a solvent Includes.
[0116] The following examples demonstrate the preparation of prepolymer components A and B.
[0117] Mixing of components A and B can be carried out by any known mixing technique, such as those described in U.S. Patent No. 6,887,401, except that components A and B are mixed in the absence of a catalyst.
[0118] The mixing can be mechanical or ultrasonic and is generally carried out at room temperature for a time ranging from 10 to 180 seconds. The components A and B to be mixed can be added in a small reaction chamber and then mixed in a screw mixer.
[0119] Preparation of polythiourethane prepolymer (component A) having isocyanate end groups A reactor equipped with a condenser, heat probe, and stirrer is charged with a predetermined amount of xylylene diisocyanate (XDI). The polyisocyanate monomer is then heated to 115° C. Next, 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane 1-thiol is introduced to obtain a molar ratio of isocyanate functional groups to thiol functional groups of 115° C.
number
[0120] The reaction is completed after 3 to 4.5 hours of heating.
[0121] The prepolymer is then cooled and once the temperature of the prepolymer reaches 35° C. (± 5° C.), it is transferred into suitable drums, blanketed with inert gas (nitrogen or argon) and stored in a cool room.
[0122] The final prepolymer (Component A) with isocyanate end groups has a viscosity of 0.219 Pa·s at 25°C.
[0123] Preparation of polythiourethane prepolymer (component B) with thiol end groups A reactor equipped with a condenser, heat probe, and stirrer is charged with a predetermined amount of 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane 1-thiol.
[0124] The polythiol monomer is then heated to 90° C. Xylylene diisocyanate (XDI) is then introduced to adjust the molar ratio of thiol groups to isocyanate groups to 90° C.
number
[0125] The reaction is complete within 3 hours, as indicated by the temperature reaching a peak and then returning to 90°C (± 2°C).
[0126] The prepolymer is then cooled and once the temperature of the prepolymer reaches 35° C. (± 5° C.), it is transferred into suitable drums, blanketed with inert gas (nitrogen or argon) and stored in a cool room.
[0127] The final prepolymer with thiol end groups (Component B) has a viscosity of 0.543 Pa·s at 25°C.
[0128] mixture (a)(iii) According to one embodiment, the fast room temperature polymerizable composition is selected from a mixture of at least one poly(iso)thiocyanate monomer and at least one liquid SH-terminated poly(thio)urethane prepolymer.
[0129] The at least one polyisocyanate or polyisothiocyanate monomer is as described above for mixture (a)(i). The at least one liquid SH-terminated poly(thio)urethane prepolymer is as described above for mixture (a)(ii) as component B.
[0130] mixture (a)(iv) According to one embodiment, the fast room temperature polymerizable composition is selected from a mixture of at least one polythiol and at least one liquid NCO or NCS terminated poly(thio)urethane prepolymer.
[0131] The at least one polythiol is as described above for mixture (a)(i). The at least one liquid NCO- or NCS-terminated poly(thio)urethane prepolymer is as described above for mixture (a)(ii) as component A.
[0132] mixture (b) According to one embodiment, the fast room temperature polymerizable composition is selected from one or more polymerizable episulfide compounds.
[0133] The episulfide compounds used in these compositions of the present disclosure are those described in the above-cited European Patent Applications A-761665 and A-785194. These episulfide compounds have the formula: [ka] and at least one of these moieties is an episulfide group.
[0134] The fast room temperature polymerizable composition of the present disclosure may contain up to 100% by weight of one or more episulfide compounds, or the polymerizable composition may contain one or more episulfide compounds and one or more copolymerizable monomers.
[0135] Among the copolymerizable monomers that can be used are the polythiol monomers described above.
[0136] Catalyst compositions useful in the present disclosure Among the catalyst compositions that may be used in the methods described herein are tertiary amines such as triethylamine, organometallic compounds such as dibutyltin dilaurate, and alkali metal, alkaline earth metal, transition metal and ammonium salts of acids or mixtures thereof, which salts satisfy the condition 0.5≦pKa≦14.
[0137] These latter salts have the formula M m P+ Y n - wherein M m P+ represents alkali metals, alkaline earth metals, transition metals and the formula NR + 4, where R is an alkyl radical; Y - is an anion such that the corresponding acid YH has a pKa satisfying the condition 0.5≦pKa≦14, p is the valence of the cation, and n = m × P.
[0138] The catalyst composition may consist solely of the salt or a mixture of these salts.
[0139] The metal cation of the salt is Li + , Na + , K + , Rb + , Mg 2+ , Ca 2+ , B.A. 2+ and Al 3+ A particularly preferred metal cation is Li because it is colorless and soluble in the composition. + , Na + and K + It is.
[0140] Transition metals are less preferred since their salts result in colored compositions and thus colored polymeric resins.
[0141] Preferred NR + The four groups are those in which R is an alkyl radical from C1 to C8, more preferably a methyl radical, an ethyl radical, a propyl radical, a butyl radical or a hexyl radical.
[0142] The salts are intended to be used in the rapidly room temperature polymerizable compositions in an effective amount, i.e., an amount sufficient to promote room temperature polymerization of the composition.
[0143] Generally, the salt is present in an amount ranging from 5 to 2000 parts per million (ppm), or from 10 to 500 ppm, or from 40 to 100 ppm, based on the total weight of polymerizable monomers.
[0144] Y - can be the anion of the corresponding acid, such as YH, which satisfies the condition 0.5≦pKa≦10, more preferably 0.5≦pKa≦8.
[0145] Anion Y -are thiocyanates, carboxylates, thiocarboxylates, acetylacetonates, diketones, acetoacetates, malonates, cyanoacetates, ketonitriles and compounds of the formula RS - where R is a substituted or unsubstituted alkyl group or a phenyl group.
[0146] The alkyl group can be a C1-C6 alkyl group, such as a methyl group, an ethyl group, and a propyl group.
[0147] Anion Y - is thiocyanate (SCN - ), acetylacetonate, acetate, thioacetate, formate and benzoate.
[0148] According to one embodiment, the salt is KSCN.
[0149] Generally, the salt is present in an amount ranging from 0.001 to 2.5%, preferably from 0.001 to 1%, based on the total weight of the polymerizable monomers. An electron donor compound may be used in combination with the salt and is selected from the group consisting of acetonitrile compounds, amide compounds, sulfones, sulfoxides, trialkyl phosphites, nitro compounds, ethylene glycol esters, crown ethers and cryptates.
[0150] Examples of acetonitrile compounds are: [ka] where R is an alkyl group, and R can be a C1 to C6 alkyl group, such as a methyl group, an ethyl group, a propyl group, or a butyl group.
[0151] The amide compound may be a primary, secondary or tertiary amide compound.
[0152] The trialkyl phosphites and triaryl phosphites have the formula: [ka] where R, R', R''' are either alkyl groups, preferably C1-C6 alkyl groups, or aryl groups such as phenyl groups. Preferred are trialkyl phosphites, such as (C2H5O)3P.
[0153] The electron donor compound may also be selected from crown ethers and cryptates.
[0154] These cyclic molecules are usually chosen to provide a good compromise between the size of the heteroatoms or metals and the "cage" size, i.e. the number of heteroatoms and their size, and the "cage" size, i.e. the number of heteroatoms and the size of the ring.
[0155] Preferred crown ethers and cryptates have the formula: [ka] wherein: X 1 represents O, S or NH, and x1 is an integer of 3 to 6, preferably 3 to 4; X 2 , X 3 and X 4 represents O or S; n2, n3, n4, y2, y3, and y4 each represent 2 or 3; and x2, x3, and x4 each represent 2 or 3.
[0156] Among the preferred crown ethers and cryptates there may be mentioned the following compounds: [ka]
[0157] The electron donor compound is present in an amount ranging from 0 to 5% by weight, preferably 0 to 1% by weight, based on the total weight of the polymerizable monomers, and is most preferably a crown ether such as 18-crown-6, 18-crown-7, 15-crown-5, 15-crown-6, etc.
[0158] In compositions containing episulfide compounds, reactivity increases with the cation size of the thiocyanate salt (potassium salts are more reactive than sodium salts, which are more reactive than lithium salts).
[0159] In compositions containing episulfide compounds, the presence of crown ethers is also highly recommended to facilitate the polymerization reaction. As the size of the crown ether increases, its reactivity appears to decrease.
[0160] According to a particular embodiment, the catalyst composition is mixed with a portion of one of the monomers used in mixture (a)(i) or (iii) or (iv), i.e., either the poly(iso)thiocyanate monomer or the polythiol monomer. The resulting composition is then deposited on at least one inner surface of the mold and / or on at least one side of the surface of the light filtering element that will later be placed in the mold assembly. The process continues by closing the mold assembly so that the inner surfaces of the mold together form a molded cavity, and filling the molded cavity of the mold assembly, which already contains the catalyst composition and said portion of one monomer deposited on at least one inner surface of the mold, with the remaining fast room temperature polymerizable composition. As used in the context of this embodiment, the remaining fast room temperature polymerizable composition includes the remaining portion of the monomer previously mixed with the catalyst and at least one other monomer described in mixture (a)(i) or the prepolymer described in mixture (a)(iii) or (iv). By way of example, the catalyst composition is further mixed with a portion of the selected polythiol, as described above, and deposited on the inner surface of the mold. Since the other monomer has not been added, the polymerization reaction cannot be initiated. The remaining portion of the polythiol is then charged along with the other monomer, i.e., the poly(iso)thiocyanate monomer, which initiates the polymerization reaction.
[0161] According to a particular embodiment, the catalyst composition is mixed with a portion of one of the prepolymers used in mixture (a)(ii), i.e., either the liquid NCO or NCS terminated poly(thio)urethane prepolymer or the liquid SH terminated poly(thio)urethane prepolymer. The resulting composition is then deposited on at least one inner surface of the mold and / or on at least one side of the surface of the light filtering element that will later be placed in the mold assembly. The process continues by closing the mold assembly so that the inner surfaces of the mold together form a mold cavity, and filling the mold cavity of the mold assembly, which already contains the catalyst composition and said portion of one prepolymer deposited on at least one inner surface of the mold, with the remaining fast room temperature polymerizable composition. When used in the context of this embodiment, the remaining fast room temperature polymerizable composition comprises the remaining portion of the prepolymer previously mixed with the catalyst and at least one other prepolymer described in mixture (a)(ii). By way of example, the catalyst composition is further mixed with a portion of the prepolymer defined above as being component B, as described above, and deposited on the inner surface of the mold. The other prepolymer, defined above as component A, has not been added and therefore cannot initiate the polymerization reaction. The remaining portion of prepolymer B is then charged together with the other prepolymer A, thereby initiating the polymerization reaction.
[0162] Further ingredients The catalyst composition used may include a solvent to facilitate dissolution of the salt catalyst.
[0163] Any polar organic compound can be used, such as acetonitrile, tetrahydrofuran or dioxane. Other suitable solvents are methanol, ethanol, thioethanol, acetone, acetonitrile and 3-methyl-2-buten-1-ol.
[0164] The amount of solvent is generally kept below 2% by weight, preferably 0-0.5% by weight or 0.0001%-0.5%, based on the total weight of polymerizable monomers present, to avoid turbidity and foaming.
[0165] The rapid room temperature polymerizable compositions of the present disclosure are also intended for casting optical articles, particularly ophthalmic lenses, in conventional proportions and may contain additives conventionally employed in polymerizable compositions, namely, inhibitors, dyes, photochromic agents, UV absorbers, fragrances, deodorants, antioxidants, anti-yellowing agents and mold release agents.
[0166] The fragrance makes it possible to mask the odor of the composition, especially during the surface treatment or processing operation by the router.
[0167] In particular, conventional UV absorbers such as those commercialized under the trade names UV5411 (registered trademark), UV9 (registered trademark), Tinuvin 400 (registered trademark), Tinuvin P (registered trademark), Tinuvin 312 (registered trademark), Seesorb 701 (registered trademark) and Seesorb 707 (registered trademark) may be used in an amount generally up to 2% by weight of the total weight of polymerizable monomers.
[0168] The compositions of the present disclosure may also include a mold release agent in an amount of up to 0.1 wt %, based on the total weight of the polymerizable monomer / prepolymer.
[0169] Among the release agents, mono- and di-alkyl phosphates, silicones, fluorinated hydrocarbons, fatty acids and ammonium salts can be mentioned.Preferred release agents are mono- and di-alkyl phosphates and their mixtures.Such release agents are described, inter alia, in U.S. Pat. No. 4,662,376, U.S. Pat. No. 4,975,328 and EP 271.839.
[0170] Light Filtering Elements According to one embodiment, the light filtering element is selected from a polarizing film, a polarizing laminate, a photochromic film, a photochromic laminate, a near infrared filter, a near infrared laminate, a blue cut filter, a blue cut filter laminate, a microstructured film, and a microstructured laminate.
[0171] As used herein, a "light filtering element" is an optical filter that limits or modifies the amount of light that passes through the element.
[0172] This filter refers to a film structure formed of either a single film layer or a film laminate structure formed of multiple film layers attached together. More precisely, the filter may be formed of an ophthalmic grade functional film (e.g., having polarizing or photochromic properties) with an ophthalmic grade protective film on one or both sides of the ophthalmic functional film. This type of multi-layer filter may also be called a laminate, wafer, or laminate wafer.
[0173] In the casting process, such a filter is placed in front of the mold cavity and the fast room temperature polymerizable composition is poured in contact with the filter. According to one embodiment, the catalyst composition is deposited on at least one surface of the filter.
[0174] According to one embodiment, the light filtering element is a polarizing film or laminate selected from the group consisting of a polarizing film of polyvinyl alcohol film (PVA), a polarizing laminate consisting of a polarizing layer supported on both sides by triacetate cellulose layers (triacetate cellulose (TAC) / polyvinyl alcohol (PVA) / triacetate cellulose (TAC) laminate), and a polarizing laminate consisting of a polarizing layer supported on both sides by polycarbonate layers (polycarbonate (PC) / polyvinyl alcohol (PVA) / polycarbonate (PC) laminate).
[0175] As used herein, PVOH and PVA may be used interchangeably.
[0176] Photochromic films or laminates are well known and contain photochromic dyes selected from the group consisting of pyrans, oxazines, fulgides and fulgimides.
[0177] Polarizing film or laminate The polarizing film or wafer can be any polarizing film or wafer that is well known in the art and is typically used to manufacture polarizing optical articles such as ophthalmic lenses.
[0178] Such filters are known and described in numerous patent documents, such as US Patent Publication No. 20070202265, US Patent Publication No. 20180052267, and US Patent Publication No. 20210268755.
[0179] Polarizing films or wafers can include a variety of different structures and materials, including free-standing or unlaminated films, films with removable protective sheets, films with permanent outer protective coatings or films with supporting plastic layers, and laminated films and wafers.
[0180] Among the polarizing films are poly(ethylene terephthalate) (PET) films and poly(vinyl alcohol) (PVOH) films.
[0181] Other polarizing films include thin multilayer polymer materials, combinations of reflective and dichroic polarizers, or mixed polymer phase films, such as those described in U.S. Pat. Nos. 5,882,774, 6,096,375, and 5,867,316.
[0182] Among the polarizing wafers are layered combinations of polycarbonate / PVOH / polycarbonate with thicknesses of less than 1 mm.
[0183] Preferably, polarized wafers are used having a thickness of more than 0.10 mm, better still 0.20 to 0.80 mm, preferably 0.30 to 0.80 mm, more preferably 0.40 to 0.80 mm.
[0184] Typically, the PVOH core film has a thickness of 0.01 to 0.04 mm, preferably 0.02 to 0.04 mm, and the two shell layers have a thickness of about 0.30 mm.
[0185] Materials other than polycarbonate for wafer construction also include poly(methyl methacrylate), polystyrene, cellulose acetate butyrate (CAB), cellulose acetate, and cellulose triacetate.
[0186] According to one embodiment, the polarizing wafer is a multi-layer combination of CAB / PVOH / CAB.
[0187] According to one embodiment, the polarizing wafer is a multi-layer combination of TAC / PVOH / TAC.
[0188] To improve the adhesion of the polarized wafer to the cured fast room temperature polymerizable composition constituting the substrate, unless otherwise stated, the wafer may be chemically treated by immersion in a 5% aqueous NaOH solution or a 1N aqueous HCl solution. The immersion time and temperature may vary widely depending on the nature of the wafer and the polymerizable composition. Typically, the immersion is carried out at a temperature in the range of 20° C. to 50° C., preferably at a temperature of about 40° C., and lasts for up to 1 hour, preferably about 30 minutes.
[0189] The polarized wafer is then rinsed in deionized water for approximately 15 seconds, then placed in warm deionized water for 1 minute, and finally rinsed again in deionized water for 15 seconds.
[0190] The polarized wafer may then be dried. Drying temperatures and times may vary widely. The hydrolyzed CAB layer becomes more hydrophilic, with a contact angle of approximately 30-35°.
[0191] Microstructured Film Alternatively or in another embodiment of the present disclosure, microstructured films or microstructured laminates can be added. Such films or laminates are known and described in many patent documents, such as EP 3895880. In applications in the lens field, they are added to control myopia, increase optical power and / or provide anti-reflective properties.
[0192] As used herein, a microstructured film is a film that has a microstructure on its surface.
[0193] As used herein, a microstructured laminate is a film having a microstructure on its surface and a coating layer formed over the film that encapsulates the microstructure of the film.
[0194] According to one embodiment, the microstructured film can be a structure that is suitably embedded in the fast room temperature polymerizable composition that constitutes the substrate. According to another complementary or alternative embodiment, the microstructured laminate can be a structure that is suitably attached onto the outer surface of the resulting substrate. Examples of microstructures include, but are not limited to, structures for controlling myopia, structures for increasing the optical power of the substrate, such as Fresnel microstructures, and structures for imparting anti-reflective properties to the substrate, such as moth-eye structures.
[0195] According to one embodiment, the microstructured film may have a thickness of 50 μm to 2 mm.
[0196] According to one embodiment, the microstructured film may include or be made of a polymer (e.g., a thermoplastic polymer). Examples of thermoplastic polymers that may be included in or that may comprise the microstructured film include, but are not limited to, polycarbonates, thermoplastic urethanes, polyacrylates, polyesters, copolyesters, polymethacrylates, polystyrenes, polyamides, polysulfones, polyphenylsulfones, polyetherimides, polypentenes, polyolefins, ionomers, ethylene methacrylic acid, cyclic olefin copolymers, acrylonitrile, and styrene maleic anhydride.
[0197] Copolymers of these polymers may also be used. Copolymers may have two or more structures in one molecule derived from different polymers. Copolymers may contain at least one structure derived from a polymer other than the above polymers.
[0198] Derivatives of the above polymers may also be used. The derivatives may have at least one functional group attached to the molecule of the above polymer.
[0199] Mixtures of these polymers, copolymers and / or derivatives may also be used. The mixture may be a resin containing two or more molecules of different polymers. The mixture may contain at least one polymer other than those mentioned above.
[0200] The film may include various additives, dyes and / or light filters. Examples of additives include, but are not limited to, heat stabilizers, release agents, HALS (hindered amine light stabilizers) and light stabilizers. Dyes can be, for example, color balance dyes, photochromic dyes, dichroic dyes. Light filters can be, for example, blue light cut dyes, UV cut dyes, IR cut dyes or any other functional components. These additives, dyes and light filters can be used alone or in any combination.
[0201] According to one embodiment, the film is transparent. The microstructure can be formed on one or both sides of the film. In one embodiment, the microstructure can be formed on one side of the film. The microstructure can be formed by any process or method. For example, the microstructure can be formed on the surface of the film by embossing the surface of the film with an embossing roll.
[0202] Microstructured Laminates According to one embodiment, the microstructure laminate is a film as described above and a coating layer formed on the film that encapsulates the microstructure of the film. In one embodiment, the coating layer completely fills the interstices of the microstructure.
[0203] The coating layer may include or be made of a polymer (e.g., a thermoplastic polymer). The above-mentioned thermoplastic polymers and copolymers and derivatives of these polymers, as well as mixtures thereof, may be used. The coating layer may also include the above-mentioned additives, dyes and / or light filters.
[0204] According to one embodiment, the coating layer is transparent.
[0205] According to one embodiment, the glass transition temperature (T1) of the film is higher than the glass transition temperature (T2) of the coating layer. Therefore, the material of the coating layer can be determined based on the material of the film, and vice versa. T1 and T2 can be 80-200°C, preferably 85-190°C, respectively, including all ranges and subranges therebetween. The difference between T1 and T2 can be 10-100°C, preferably 12-75°C, including all ranges and subranges therebetween.
[0206] For example, if the film is made of or includes polycarbonate, the coating layer may be made of or includes polymethylmethacrylate. If the film is made of or includes polysulfone, the coating layer may be made of or includes polyester. If the film is made of or includes copolyester, the coating layer may be made of or includes polymethylmethacrylate. If the film is made of or includes polyamide, the coating layer may be made of or includes polymethylmethacrylate. If the film is made of or includes copolyester, the coating layer may be made of or includes thermoplastic urethane. The film and the coating layer may also be made of the same polymer, as long as the glass transition temperature (T1) of the film is higher than the glass transition temperature (T2) of the coating layer. For example, if the film is made of or includes a polyamide, the coating layer may be made of or include a polyamide having a glass transition temperature lower than that of the polyamide in the film. These combinations are provided by way of example only, and the material combinations of the film and coating layer are not particularly limited, as long as the glass transition temperature (T1) of the film is higher than the glass transition temperature (T2) of the coating layer.
[0207] According to one embodiment, the refractive index of the coating layer (n2) is different from the refractive index of the film (n1), where n1 and n2 can each be from 1.45 to 1.65, preferably from 1.49 to 1.64, including all ranges and subranges therebetween.
[0208] The thickness (h2) of the coating layer can be determined based on the size of the microstructures on the surface of the film and / or the thickness (h1) of the film, and the elastic modulus of the film and the coating layer.
[0209] Minimum coating layer thickness (h 2,min) is equal to the height of the microstructure on the film surface, or formula (1) h 2(min) =h1×(E1 / E2), whichever is greater, where E1 is the elastic modulus of the film and E2 is the elastic modulus of the coating layer.
[0210] The coating layer can be made thick enough so that the microstructures on the surface of the film are substantially or completely embedded in the coating layer.
[0211] Maximum thickness of coating layer (h 2,max ) is not particularly limited and can be determined depending on the application of the laminate.
[0212] The material of the coating layer can have good compatibility with the material of the film so that the coating layer is strongly adhered to the film. In one embodiment, the coating layer can be bonded to the film such that the peel strength between the film and the coating layer (measured by the test method of ASTM D1876-01) is at least 100g / 25mm.
[0213] According to one embodiment, both the microstructured films and microstructured laminates described above can be deformed into an optimal shape by application of heat, pressure, or both.
[0214] The deformation can be carried out, for example, by a thermoforming process using a thermoforming machine or an injection molding process using an insert. During deformation, the laminate can be inserted into a mold so that pressure is applied directly to the coating layer of the laminate. A polymer lens can be inserted into the mold together with the laminate so that the laminate is injection molded with the polymer lens. The polymer lens can be made of or contain the material of the film. The laminate can be inserted into the mold in contact with the insert and a hot polymer melt can be injection molded onto the laminate. The same applies to microstructured films.
[0215] The deformation can be performed at a temperature lower than the glass transition temperature (T1) of the film. In one embodiment, the deformation can be performed at a temperature near the glass transition temperature (T2) of the coating layer and lower than the glass transition temperature (T1) of the film. By performing the deformation at such a temperature, the laminate can be deformed, but the microstructure formed on the surface of the film is not deformed. The same applies to the microstructure film.
[0216] According to one aspect, the present disclosure relates to an optical article produced by the method of the first aspect.
[0217] According to one aspect, the present disclosure relates to an ophthalmic lens manufactured by the method of the first aspect.
[0218] The transparent ophthalmic lenses manufactured according to one embodiment of the present disclosure represent ophthalmic lenses selected from blank lenses, semi-finished lenses, finished lenses and lenses fitted to a see-through "head mounted display" (HMD), by which is understood a device that can be mounted on the head of a wearer and that comprises an optical imager that shapes the light beam coming from an electronic and optical system that generates the light beam from an electronic signal, the system being of the small screen, laser diode or light emitting diode (LED) type, the optical imager directing the light beam to the wearer's eye to make the information content available.
[0219] The transparent ophthalmic lens may be a lens selected from afocal (or non-corrective or plano), monofocal, bifocal, trifocal and progressive lenses, and the ophthalmic lens may be mounted either in a conventional frame or in a mask, visor, helmet sight or goggles that includes two separate ophthalmic lenses, one for the right eye and the other for the left eye, one ophthalmic lens facing the right and left eye simultaneously, and the ophthalmic lens may be manufactured in a conventional geometric shape as a circle or may be manufactured to fit into a geometric shape that matches the intended frame. If the ophthalmic lens is dedicated for mounting to a see-through "HMD", the lens may be a corrective lens or an afocal lens and may be placed in front of and / or behind the optical imager of the HMD. If the ophthalmic lens is placed in front of and behind the optical imager, this means that the optical imager is inserted inside the ophthalmic lens.
[0220] "Ophthalmic lens" is defined according to the present disclosure as a lens intended to be attached to spectacles, i.e., having the function of protecting the eye and / or correcting vision. The lens is selected from afocal, monofocal, bifocal, trifocal and progressive lenses. It should therefore be understood that the ophthalmic lens can be corrective or non-corrective. The spectacles to which the ophthalmic lens is attached can be either a conventional frame with two different ophthalmic lenses, one for the right eye and one for the left eye, or a similar mask, visor, helmet sight or goggles, with one ophthalmic lens facing both eyes at the same time. The ophthalmic lens produced by the method of the present disclosure can be produced as a circular shape with a conventional geometric shape, or can be produced to fit into the intended frame.
[0221] The ophthalmic lenses produced according to the method of the present disclosure can be further functionalized, optionally in a further step after the post-processing step, by adding at least a functional coating and / or a functional film. The functionality can be added to one side or surface of the ophthalmic lens or to two sides of the ophthalmic lens, the functionality can be the same or different on each side. Among the functionalities, by way of example and without limitation, we can mention functionalities selected from impact resistance, abrasion resistance, antifouling, antistatic, antireflective, antifog, rainproof, self-healing, polarization, tinting, photochromic, selective wavelength filters that can be obtained by absorption or reflection filters. Such selective wavelength filters are particularly intended for filtering, for example, ultraviolet radiation, blue light radiation or infrared radiation.
[0222] The functionality may be added by at least one process selected from dip coating, spin coating, spray coating, vacuum deposition, transfer process or lamination process. By transfer process, it is understood that the functionality is first deposited on a support such as a carrier and then transferred from said carrier to said ophthalmic lens via an adhesive layer deposited between the two elements. Lamination is defined as obtaining a permanent contact between a film having at least one functionality as described herein above and the surface of the ophthalmic lens to be treated, said permanent contact being obtained by establishing contact between said film and said lens, followed by an optional polymerization or heating step to finalize the adhesion and fixation between the two entities. At the end of this lamination step, the assembled film and optical lens form a single entity. In the lamination process, an adhesive is usually present at the interface between the film and the ophthalmic lens. An example of this is detailed above in relation to the microstructured laminate added to one or both faces or surfaces of the ophthalmic lens. EXAMPLES
[0223] Example 1 A catalyst solution containing 0.191 g of 18-crown-6, 0.048 g of KSCN, and 0.318 g of thioethanol is spin-coated onto the cc surface of the cx mold. Then, 10.00 g of NCO-terminated prepolymer xylylene diisocyanate (viscosity equal to 0.071 Pa·s at 25°C) prepared with an NCO / SH ratio of 8 / 1 is mixed with 9.39 g of SH-terminated prepolymer 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane-1-thiol (viscosity equal to 0.543 Pa·s at 25°C) prepared with an SH / NCO ratio of 8 / 1, and the mixture is filled into the mold assembly.
[0224] Gelation occurs in less than 10 minutes at room temperature and the reaction is complete in 2 hours at 135°C in an air oven.
[0225] Example 2 A catalyst solution containing 0.191 g of 18-crown-6, 0.048 g of KSCN, and 0.318 g of thioethanol is spin-coated onto the cx surface of the cc mold. Then, 10.00 g of NCO-terminated prepolymer xylylene diisocyanate prepared with an 8 / 1 NCO / SH ratio (viscosity equal to 0.071 Pa·s at 25°C) is mixed with 9.39 g of SH-terminated prepolymer 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane-1-thiol prepared with an 8 / 1 SH / NCO ratio (viscosity equal to 0.543 Pa·s at 25°C) and the mixture is filled into the mold assembly. Gelling occurs in less than 10 minutes at room temperature, and the reaction is completed in 2 hours at 135°C in an air oven.
[0226] Example 3 A catalyst solution containing 0.191 g of 18-crown-6, 0.048 g of KSCN, and 0.318 g of thioethanol is prepared. 50% of this solution is spin-coated onto the cc surface of the cx mold, and 50% of this solution is spin-coated onto the cx surface of the cc mold. Then, 10.00 g of NCO-terminated prepolymer xylylene diisocyanate (viscosity equal to 0.071 Pa·s at 25°C) prepared with an NCO / SH ratio of 8 / 1 is mixed with 9.39 g of SH-terminated prepolymer 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane-1-thiol (viscosity equal to 0.543 Pa·s at 25°C) prepared with an SH / NCO ratio of 8 / 1, and the mixture is filled into the mold assembly. Gelling occurs in less than 10 minutes at room temperature, and the reaction is completed in 2 hours at 135°C in an air oven.
[0227] Example 4 A catalyst solution containing 0.191 g of 18-crown-6, 0.048 g of KSCN, and 0.318 g of thioethanol is prepared. 50% of this solution is spin-coated onto the cc surface of the polarizing film, and 50% of this solution is spin-coated onto the cx surface of the polarizing film. The polarizing film is then placed into the mold assembly.
[0228] 10.00 g of NCO-terminated prepolymer xylylene diisocyanate (viscosity equal to 0.071 Pa·s at 25° C.) prepared with an NCO / SH ratio of 8 / 1 is mixed with 9.39 g of SH-terminated prepolymer 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane-1-thiol (viscosity equal to 0.543 Pa·s at 25° C.) prepared with an SH / NCO ratio of 8 / 1, and the mixture is filled into the mold assembly. Gelling occurs in less than 10 minutes at room temperature and the reaction is completed in 2 hours at 135° C. in an air oven.
[0229] Example 5 A catalyst solution containing 0.191 g of 18-crown-6, 0.048 g of KSCN, 0.318 g of thioethanol, and 0.760 g of N,N-dicyclohexylmethylamine is prepared. 50% of this solution is spin-coated onto the cc surface of the cx mold, and 50% of this solution is spin-coated onto the cx surface of the cc mold. Then, 10.00 g of NCO-terminated prepolymer xylylene diisocyanate (viscosity equal to 0.071 Pa·s at 25°C) prepared with an NCO / SH ratio of 8 / 1 is mixed with 9.39 g of SH-terminated prepolymer 3-(2-sulfanylethylthio)-2-(2-sulfanylethylthio)propane-1-thiol (viscosity equal to 0.543 Pa·s at 25°C) prepared with an SH / NCO ratio of 8 / 1, and the mixture is filled into the mold assembly. Gelation occurs in less than 10 minutes at room temperature and the reaction is complete in 2 hours at 135°C in an air oven.
[0230] Example 6 A catalyst solution containing 0.012 g of 18-crown-6, 0.003 g of KSCN, and 0.318 g of thioethanol is spin-coated onto the cc surface of the cx mold. Then, 10.00 g of xylylene diisocyanate monomer is mixed with 9.23 g of 1,2-bis(2'-mercaptoethylthio)-3-mercaptopropane monomer, and the mixture is filled into the mold assembly. Gelling occurs in less than 10 minutes at room temperature, and the reaction is completed in 2 hours at 120°C in an air oven.
[0231] Example 7 A catalyst solution containing 0.012 g of 18-crown-6, 0.003 g of KSCN, and 0.318 g of thioethanol is prepared. 50% of this solution is spin-coated onto the cc surface of the cx mold, and 50% of this solution is spin-coated onto the cx surface of the cc mold. Next, 10.00 g of xylylene diisocyanate monomer is mixed with 9.23 g of 1,2-bis(2'-mercaptoethylthio)-3-mercaptopropane monomer, and the mixture is filled into the mold assembly. Gelling occurs in less than 10 minutes at room temperature, and the reaction is completed in 2 hours at 120°C in an air oven.
[0232] Example 8 A catalyst solution containing 0.035 g of 15-crown-6, 0.002 g of LiSCN, and 0.318 g of acetonitrile is spin-coated onto the cc surface of the cx mold. Then, 10.00 g of xylylene diisocyanate monomer is mixed with 12.99 g of tetrakis mercaptopropionate pentaerythritol monomer, and the mixture is filled into the mold assembly. Gelling occurs in less than 10 minutes at room temperature, and the reaction is completed in 2 hours at 120° C. in an air oven.
[0233] Example 9 A catalyst solution containing 0.008 g of 18-crown-6, 0.002 g of KSCN, 0.318 g of thioethanol, and 0.030 g of N,N-dicyclohexylmethylamine is spin-coated onto the cc surface of the cx mold. 20.00 g of bis(β-epithiopropyl)sulfide monomer is then loaded into the mold assembly. Gelling occurs in less than 1 hour at 45° C., and the reaction is completed in 2 hours at 80° C. in an air oven.
[0234] Although representative processes and articles have been described in detail herein, those skilled in the art will recognize that various substitutions and modifications may be made without departing from the scope of what is described and defined by the appended claims.
Claims
1. 1. A method for fast curing a transparent cast substrate that can be used to make optical articles such as ophthalmic lenses, comprising: - providing a fast room temperature polymerizable composition; - providing a catalyst composition; - providing a mould assembly comprising two non-sealing moulds each having an inner surface and an outer surface, and optionally providing an optical filtering element disposed or adapted to be disposed between said two non-sealing moulds; - said catalyst composition on the inner surface of at least one of the two non-closed moulds, and / or on at least one surface of the light filtering element that is subsequently placed in the mold assembly. and depositing the - closing the mold assembly so that the inner surfaces of the two non-closed molds together form a molding cavity; - filling the mold cavity of the mold assembly, which already contains the catalyst composition deposited on the inner surface of at least one of the two non-closed molds, with the fast room temperature polymerizable composition; - hardening the filled mold assembly to obtain a transparent solid substrate, a) a first step for polymerizing said rapidly room temperature polymerizable composition at room temperature to obtain a gel; b) a second step of post-curing said gel to obtain said transparent solid substrate; and - recovering said transparent solid substrate from said mold assembly; The method includes:
2. The method of claim 1 , wherein depositing the catalyst composition onto the inner surface of at least one of the two non-closed molds and / or onto at least one side of the light filtering element is performed by liquid deposition.
3. 3. The method of claim 1 or 2, wherein depositing the catalyst composition onto the inner surface of at least one of the two non-closed molds and / or onto at least one side of the light filtering element is performed by spin coating, dip coating, spray coating, brush coating or roller coating.
4. The method according to any one of claims 1 to 3, wherein the rapidly room temperature polymerizable composition has a viscosity in the range of 0.1 to 0.3 Pa·s at 25°C.
5. The fast room temperature polymerizable composition comprises (a) at least one poly(iso)thiocyanate monomer or liquid NCO- or NCS-terminated poly(thio)urethane prepolymer, and at least one polythiol monomer or liquid SH-terminated poly(thio)urethane prepolymer; or (b) One or more polymerizable episulfide compounds The method according to any one of claims 1 to 4, wherein the composition is selected from the group consisting of
6. The mixture (a) is a first component A comprising a polythiourethane prepolymer having isocyanate or isothiocyanate (NCX, where X is O or S) end groups and a viscosity in the range of 0.02 to 0.4 Pa·s at 25° C.; a second component B comprising a polythiourethane prepolymer having thiol (SH) end groups and a viscosity in the range of 0.2 to 2.0 Pa·s at 25° C.; Including, 6. The method of claim 5, wherein components A and B are obtained by polymerizing at least one polyisocyanate or polyisothiocyanate monomer and at least one polythiol monomer.
7. 7. The method according to claim 5 or 6, wherein the amounts of polyisocyanate or polyisothiocyanate monomers and polythiol monomers are such that the ratio NCX / SH in the mixture of polyisocyanate or isothiocyanate monomers and polythiol monomers ranges from 4:1 to 30:1 to obtain component A, and the ratio SH / NCX in the mixture of polyisocyanate or isothiocyanate monomers and said polythiol monomers ranges from 4:1 to 30:1 to obtain component B.
8. The polythiol has the formula: R'(SH)n' (wherein n' is an integer from 2 to 6, preferably 3 to 4, and R' is an organic group having a valence equal to n'). The method according to any one of claims 5 to 7, comprising:
9. The polythiol may be pentaerythritol tetrakis mercaptopropionate, 1-(1'mercaptoethylthio)-2,3-dimercaptopropane, 1-(2'-mercaptopropylthio)-2,3-dimercaptopropane, 1-(-3'mercaptopropylthio)-2,3-dimercaptopropane, 1-(-4'mercaptobutylthio)-2,3-dimercaptopropane, 1-(5'mercaptopentylthio)-2,3-dimercaptopropane, 1-(6'-mercaptohexylthio)-2,3-dimercaptopropane, 1,2-bis(-4'-mercaptobutylthio)-3-mercaptopropane, 1,2-bis(-5'mercaptopentylthio)-3-mercaptopropane, 1,2-bis(-6'-mercaptohexylthio)- 9. The method of claim 8, wherein the mercapto group is selected from the group consisting of 3-mercaptopropane, 1,2,3-tris(mercaptomethylthio)propane, 1,2,3-tris(-3'-mercaptopropylthio)propane, 1,2,3-tris(-2'-mercaptoethylthio)propane, 1,2,3-tris(-4'-mercaptobutylthio)propane, 1,2,3-tris(-6'-mercaptohexylthio)propane, methanedithiol), 1,2-ethanedithiol, 1,1-propanedithiol, 1,2-propanedithiol, 1,3-propanedithiol, 2,2-propanedithiol, 1,6-hexanethiol-1,2,3-propanetrithiol, and 1,2-bis(-2'-mercaptoethylthio)-3-mercaptopropane.
10. The polyisocyanate or polyisothiocyanate has the formula: 【Chemistry 1】 is selected from monomers of the formula: R 1 are independently H or C 1 ~C 5 Alkyl group, preferably CH 3 Or C 2 H 5 and R 2 is H, a halogen, preferably Cl or Br, or C 1 ~C 5 Alkyl group, preferably CH 3 Or C 2 H 5 and Z is -N=C=X, X is O or S; a is an integer ranging from 1 to 4, b is an integer ranging from 2 to 4, and a+b≦6; and The method according to any one of claims 5 to 9, wherein x is an integer from 1 to 10, preferably from 1 to 6.
11. The polyisocyanate or isothiocyanate may be tolylene diisocyanate or diisothiocyanate, phenylene diisocyanate or diisothiocyanate, ethyl phenylene diisocyanate, isopropyl phenylene diisocyanate or diisothiocyanate, dimethyl phenylene diisocyanate or diisothiocyanate, diethyl phenylene diisocyanate or diisothiocyanate, diisopropyl phenylene diisocyanate or diisothiocyanate, trimethyl benzyl triisocyanate or triisothiocyanate. , xylylene diisocyanate or diisothiocyanate, benzyl triiso(thio)cyanate, 4,4'-diphenylmethane diisocyanate or diisothiocyanate, naphthalene diisocyanate or diisothiocyanate, isophorone diisocyanate or diisothiocyanate, bis(isocyanate or isothiocyanatomethyl)cyclohexane, hexamethylene diisocyanate or diisothiocyanate, and dicyclohexylmethane diisocyanate or diisothiocyanate.
12. The fast room temperature polymerizable composition has the formula: 【Chemistry 2】 wherein X is S or O.
13. 13. The method of any one of claims 1 to 12, wherein the light filtering element is selected from a polarizing film, a polarizing laminate, a photochromic film, a photochromic laminate, a near infrared filter, a near infrared laminate, a blue cut filter, a blue cut laminate, a microstructured film, and a microstructured laminate.
14. The catalyst composition comprises: tertiary amines such as triethylamine, Organometallic compounds such as dibutyltin dilaurate, A compound selected from alkali metal, alkaline earth metal, transition metal and ammonium salts of an acid or mixtures thereof It consists of: The method according to any one of claims 1 to 13, wherein the salt satisfies the condition 0.5≦pKa≦14.
15. An optical article produced by the method according to any one of claims 1 to 14.
Citation Information
Patent Citations
Production of plastic lens
JP1997005680A
Polymerizable composition for producing sulfur-containing resin containing salt catalyst and method for producing molded product of sulfur-containing resin
JP2002528613A
Method for manufacturing plastic lens
JP2010105395A
Process for Manufacturing a Polarized Poly(thio)urethane Optical Lens
US20070202265A1
Polymerizable composition for optical material and optical material
WO2015060259A1